2012
DOI: 10.1093/ntr/ntr302
|View full text |Cite
|
Sign up to set email alerts
|

Comparing an Immediate Cessation Versus Reduction Approach to Smokeless Tobacco Cessation

Abstract: Our study demonstrated that immediate cessation with an established quit date resulted in greater cessation success than a gradual reduction approach among ST users who do not have an immediate quit plan but are motivated to quit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Only data collected during baseline from each study were used in the analysis. Studies 1 -5 have been described elsewhere ( Ebbert, Edmonds, Luo, Jensen, & Hatsukami, 2010 ;Hatsukami et al, 2007Hatsukami et al, , 2008Hatsukami et al, , 2004Schiller, Luo, Anderson, Jensen, & Hatsukami, 2012 ). Briefl y, Studies 1 -4 recruited adult (18-to 70 -year -old) ST users who were interested in reducing use but not quitting in the next 90 days; Study 1 only recruited those who were using Copenhagen or Kodiak Wintergreen brand ST products.…”
Section: Methodsmentioning
confidence: 99%
“…Only data collected during baseline from each study were used in the analysis. Studies 1 -5 have been described elsewhere ( Ebbert, Edmonds, Luo, Jensen, & Hatsukami, 2010 ;Hatsukami et al, 2007Hatsukami et al, , 2008Hatsukami et al, , 2004Schiller, Luo, Anderson, Jensen, & Hatsukami, 2012 ). Briefl y, Studies 1 -4 recruited adult (18-to 70 -year -old) ST users who were interested in reducing use but not quitting in the next 90 days; Study 1 only recruited those who were using Copenhagen or Kodiak Wintergreen brand ST products.…”
Section: Methodsmentioning
confidence: 99%
“…Only one study of behavioral pathways to abstinence among substance users was found in the literature to date, conducted with a population of smokeless tobacco users with no immediate plans to quit (Schiller et al, 2012), and compared the efficacy of an immediate quit strategy to gradual reduction of use to a quit date. Participants were randomized to immediate cessation or to a reduction condition (choice of nicotine lozenge or brand switching to help them reduce their use or levels of nicotine exposure, with a quit date of six weeks after study onset).…”
Section: Introductionmentioning
confidence: 99%
“…6,7,21 Two studies statistically assessed the relationship between flavored tobacco use and age by examining age as a dichotomous variable. 7,18 Villanti et al 7 found that younger age (18)(19)(20)(21)(22)(23)(24) was significantly associated with flavored tobacco use when compared with older age (25)(26)(27)(28)(29)(30)(31)(32)(33)(34), while Vander Weg et al 18 found no relationship between younger age (<20 years old) and flavored tobacco use when compared with older age (≥20 years old). This inconsistency may be due to the different samples (a nationally representative sample vs. military recruits, who may be more inclined toward tobacco than the general population).…”
Section: Flavored Tobacco Use and Agementioning
confidence: 99%
“…22,23 Two studies examined other measures related to flavored tobacco use and age. 19,20 Oliver et al combined data from five previously conducted treatment or switching studies [24][25][26][27][28] and found no significant differences between current flavored and nonflavored smokeless tobacco users with regard to their mean age of first dip or mean age of daily/regular use. 20 Soldz et al 19 found that the mean age of initiation for current kretek users was significantly higher than that for cigarettes and cigars, and there was no significant difference in mean age of initiation when compared to bidis.…”
Section: Flavored Tobacco Use and Agementioning
confidence: 99%